Hubungan Antara Beban Kerja Pemetik Teh Dengan Kejadian Nyeri Otot Upper Trapezius Di Perkebunan Teh Kemuning Tawangmangu - Untung, Muhammad; , Agus Widodo, S.Fis., M.Fis; , Dwi Kurniawati, SST.FT, M.Kes (2015)
Background: Workers picking tea leaves at a tea plantation is done every day for 6 hours dengen holding a result of the passage allows experiencing pain Upper trapezius muscle. This is due to the heavy burden that carried the tea leaves can reach more than 60-100 kg within one working day. Objective: Is there a relationship between Workload with Genesis Tea Picker Upper trapezius muscle pain in Myrtle Tea Plantation Benefits Research: Increase knowledge and determine whether there is a relationship work period of the trends affected picking tea Upper trapezius muscle pain. Methods: This study was conducted in June 2015. The survey method type non experiment research, with cross sectional approach. A sample of 41 workers in the tea plantations yellow, with accidental sampling technique, using a research instrument with VDS pain measurement, while the workload using a questionnaire. Data analysis using Chi Square test. Results: Results showed 23 respondents with a carrying load <80 kg, and 18 respondents with a load carrying 81-100 kg of tea leaves. 25 respondents experienced mild pain at Upper trapezius muscle, and 18 respondents had moderate pain at Upper trapezius muscle. Chi square test results obtained p = 0.029. OR = 4.78 Conclusion: is there a relationship between tea pickers work load with the incidence of upper trapezius muscle pain in yellow tea plantations. Tea pickers workers with work load of more than 80 kg had 4.78 times greater risk of experiencing pain Upper trapezius muscle in the tea pickers workers appeal to the workload of less than 80 kg. Keywords: workload, upper trapezius muscle aches, tea pickers